Electrical Conductivity of Fine Crystalline Graphite under the Influence of the Hydrostatic Pressure - I.V. Ovsiienko; L.Yu. Matzui; O.I. Prokopov; O.V. Zhuravkov (Журнал нано- та електронної фізики)
It was investigated the influence of hydrostatic pressure on the electrical conductivity of crystalline graphite in temperature range (77-293) K. It was revealed that the reducing of electrical resistivity in specimens of fine crystalline graphite under the action of hydrostatic pressure is due to increasing of overlap between valence and conduction bands that leads to increase of the concentration of free charge carriers. The change of the overlap of valence and conduction bands was estimated. It is shown the decrease of the distance between the graphite layers under pressure is irreversible process, when load is remove the electric resistance increases slightly, but does not acquire the initial value.